Penguatan Literasi Keuangan Digital pada Masyarakat di Lingkungan Babakan Gerung - Putu Ita Lestari; Ni Putu Sasmika Dewi; Sri Rahayu Puspawati; I Komang Widya Purnama Yasa (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
The "Strengthening Digital Financial Literacy in the Babakan Gerung Community" program aims to increase public understanding of the safe and effective use of digital wallets. With the advancement of digital technology, the use of digital wallets such as ShopeePay, Dana, OVO, and LinkAja is growing. However, some residents, particularly in Babakan Gerung, still have limited understanding of the security features and potential risks associated with using these applications. This activity was carried out through four main stages: data collection, outreach, education, and mentoring. Data collection was conducted to identify digital wallet users and explore their experiences with digital fraud. The education program involved inviting resource persons to provide understanding on how to safely use digital wallets, including setting up two-step verification and protecting personal data. The mentoring program aimed to help the community understand how to secure their accounts and conduct transactions safely. Evaluations showed that after participating in the education and mentoring, most participants felt more confident and prepared to use digital wallets wisely. The evaluation also indicated that the program was successful in increasing digital financial literacy and reducing the community's reliance on cash transactions